Chemical Characterization of Water-soluble Ions and Metals in Particulate Matter Generated by a Portable Two-stroke Gasoline Engine - Jen-Hsiung Tsai; Shui-Jen Chen; Sheng-Lun Lin; Zheng-You Xu; Kuo-Lin Huang; Chih-Chung Lin (Aerosol and Air Quality Research)
Abstract To examine the characteristics of water-soluble ions and metals on the particulate matter (PM) in the exhausts, a P2SGE (portable two-stroke gasoline engine) was fueled by unleaded gasoline #92 blended with different two-stroke engine oil brands (CPC Super Low Smoke Two-Stork Engine Oil (SLS), CPC Low Smoke Two-Stroke Engine Oil (LS), and MERCURY STAR (MS)) and operated under idling, mid-load (1.5 kW), and high-load (1.9 kW), respectively. Experimental results reveal that the PM mass concentrations in the exhausts were in the order MS (avg. 1,934 mg Nm−3) > SLS (avg. 1,543 mg Nm−3) > LS (avg. 1,167 mg Nm−3) in all test conditions. The mass concentrations and emission factors (EFs) of PM decreased as the P2SGE load increased by adding each tested lubricant. Based on fuel consumption, EFs of ΣIons were the lowest when utilizing the LS additive (avg. 89.7 mg L-fuel−1), followed by the MS and SLS (165 and 168 mg L-fuel−1, in average, respectively); whereas the lowest levels of ΣMetals were observed by using MS additive (avg. 61.3 mg L−1), followed by using the LS (avg. 83.8 mg L−1) and SLS (avg. 85.2 mg L−1). The soluble ions on the PM were mostly Na+, Ca2+, NO3 −, and SO4 2− among eight tested species, which accounted for only 0.05–0.19% (avg. 0.1%) of PM mass. The 21 analyzed metal components represented only 0.05% of the mass of the PM, and were dominated by Na, Mg, Al, K, Ca, Fe, and Zn, which represented 98.7% by mass of ΣMetals. Our finding for portable engine emission has been rarely considered in the literature but it is unneglectable for labors who are usually exposed to the ions and metals. Further health risk assessment research is suggested to include temporarily real-life exposures with high pollutant levels.